A Review of Composite Lithium Metal Anode for Practical Applications. Issue 1 (12th November 2019) - Shi, Peng; Zhang, Xue‐Qiang; Shen, Xin; Zhang, Rui; Liu, He; Zhang, Qiang
Abstract: Lithium (Li) metal is considered as a promising anode candidate for next‐generation batteries owing to its extremely high specific capacity and low reduction potential. However, Li metal anode is still hindered by uncontrolled Li dendrites and extreme volume fluctuation. Composite Li metal anode emerges as an attractive strategy to suppress Li dendrites and relieve volume fluctuation by regulating the behaviors of Li plating/stripping. Although progresses are visible in composite Li anode with much excess Li (>50 mAh cm −2 ), high negative/positive capacity ratio (>50), and low current density (<1 mA cm −2 ), yet the suppression of Li dendrites and long lifespan of practical Li batteries are still challenged with limited Li (<10 mAh cm −2 ), low negative/positive capacity ratio (<3), and high current density (>3 mA cm −2 ). Here, the progresses of composite Li anode are reviewed in terms of the material types, structures, and fabrications of composite Li anode in order to promote the substantial developments of practical Li batteries. Furthermore, the perspectives of current challenges and further rational designs of composite Li anode are presented aiming to bring new avenues for high‐energy‐density practical Li batteries. Abstract : The composite lithium anodes are reviewed in terms of the material types, structures, and fabrications of composite anode in order to promote the substantial developments of practical lithium batteries. The perspectives of current challenges and further rational designs of composite lithium anode are presented aiming to bring new avenues for high‐energy‐density practical lithium batteries.